A new approach to the experimental determination of the critical temperature of metamagnets - Salem-Sugui, S. [UNESP]; Ortiz, W. A. [UNESP] (Elsevier, 1986)
A new approach to the experimental determination of the critical temperature of metamagnetic samples with non-zero demagnetizing factors is presented. The method is applied to metamagnetic Ni(NO3)2·2H2O, allowing the conclusion that this salt exhibits a tricritical point. Pressure dependence of the critical temperature, and the existence of a pressure-induced metamagnetic transition are also reported. © 1986.
Keywords: NICKEL COMPOUNDS - Magnetic Properties; CRITICAL TEMPERATURE; MAGNETIC MATERIALS